2017
DOI: 10.3389/fpls.2017.00897
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Tomato Uncovers an Involvement of Cytochrome P450s and Peroxidases in Stigma Color Formation

Abstract: Stigma is a crucial structure of female reproductive organ in plants. Stigma color is usually regarded as an important trait in variety identification in some species, but the molecular mechanism of stigma color formation remains elusive. Here, we characterized a tomato mutant, yellow stigma (ys), that shows yellow rather than typical green color in the stigma. Analysis of pigment contents revealed that the level of flavonoid naringenin chalcone was increased in the ys stigma, possibly as a result of higher ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 80 publications
(136 reference statements)
0
9
0
Order By: Relevance
“…In a rice indica cultivar, its purple apiculi and stigma were genetic regulated by the interaction of two genes involved the anthocyanin biosynthesis pathway: OsC1 (encoding a R2R3-MYB transcription factor) and OsDFR (encoding a dihyroflavonol 4-reductase) ( Meng et al., 2021 ). Recent two transcriptomic studies aimed at revealing the gene network were conducted and showed that the yellow stigma in tomato is very likely due to the accumulation of yellow-colored flavonoid naringenin chalcone, whereas the melon yellow stigma is due to break-down of chloroplast structure interfering chlorophyll biosynthesis ( Zhang et al., 2017 ; Lv et al., 2022a ). Despite the crucial functional roles of stigmas play in plant reproduction, there has not been sufficient researches dedicated to the color of stigma.…”
Section: Introductionmentioning
confidence: 99%
“…In a rice indica cultivar, its purple apiculi and stigma were genetic regulated by the interaction of two genes involved the anthocyanin biosynthesis pathway: OsC1 (encoding a R2R3-MYB transcription factor) and OsDFR (encoding a dihyroflavonol 4-reductase) ( Meng et al., 2021 ). Recent two transcriptomic studies aimed at revealing the gene network were conducted and showed that the yellow stigma in tomato is very likely due to the accumulation of yellow-colored flavonoid naringenin chalcone, whereas the melon yellow stigma is due to break-down of chloroplast structure interfering chlorophyll biosynthesis ( Zhang et al., 2017 ; Lv et al., 2022a ). Despite the crucial functional roles of stigmas play in plant reproduction, there has not been sufficient researches dedicated to the color of stigma.…”
Section: Introductionmentioning
confidence: 99%
“…A number of well-designed experiments in genome-wide transcriptome analysis for identifying differentially expressed genes and/or AS in tomato, a model plant specifically for fruit development, have been reported in recent few years. These studies include comparative transcriptome analysis of domesticated tomato for identifying differentially expressed genes in different tissues (Lopez-Casado et al, 2012; Koenig et al, 2013; Zouine et al, 2014; Sun and Xiao, 2015; Sundaresan et al, 2016; Wang K. et al, 2016; Zhang Y. et al, 2017), diurnal transcriptome changes (Higashi et al, 2016), global transcriptome profiles of tomato leaf responses to exogenous ABA or cytokinin (Wang et al, 2013; Shi et al, 2013), root transcriptome regulations in response to different plant hormone cytokinin and auxin (Gupta et al, 2013), transcriptome profiles with a focus on fruit development or in different fruit tissues (Ye et al, 2015; Zhang S. et al, 2016; Dai et al, 2017; Ezura et al, 2017) and fruit chilling tolerance (Cruz-MendĂ­vil et al, 2015). RNA-seq data were also collected for analysis of differential gene expressions in response to tomato yellow leaf curl virus (TYLCV) infection in the TYLCV-resistant (R) breeding line and TYLCV-susceptible breeding line (Chen et al, 2013), in response to tobacco rattle virus (TRV) (Zheng et al, 2017), Pseudomonas syringae (Yang et al, 2015; Worley et al, 2016), Xanthomonas perforans (Du et al, 2015), Cladosporium fulvum (Xue et al, 2016), Colletotrichum gloeosporioides (Alkan et al, 2015), Verticillium dahlia (Tan et al, 2015), Meloidogyne incognita (root-knot nematode) (Shukla et al, 2018) and in arbuscular mycorrhiza inoculated and control plants (Zouari et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In plants, P450s are involved in metabolism processes related to pigment formation, defence response, photosynthesis, respiration, etc [ 37 ]. In tomato, Zhang et al [ 38 ] found that two cytochrome P450s regulate yellow stigma formation by indirectly enhancing the biosynthesis of yellow-coloured naringenin chalcone in the stigma of tomato. Fatty acid metabolism not only produces energy but also provides a carbon skeleton for organic compound formation.…”
Section: Discussionmentioning
confidence: 99%